Analisis Keterbacaan dan Efisiensi Pada Logo HUT 76 Lombok Tengah - Kharismanata, I Gede Anjas; Lazuardi, Azhar Banyu; Qatrunnada (CV Insan Kreasi Media, 2024)
The quality of the 76-year-old Central Lombok logo is considered to lack good readability and efficiency. This can affect the quality of the audience’s readability in understanding the visuals. Moreover, Central Lombok is a mirror reflection of Indonesia at international scale MotoGP events and is required to develop regional branding. The aim of this research is to analyze the level of readability and efficiency through analyzing the use of color and the application of typography in the logo. The method used in this research uses quantitative methods with research stages including the data collection process through digital observation on the diskominfoloteng Instagram. In the research results, the error in choosing colors in the 76 Central Lombok logo by using red and white in the logo, where the two colors have very different color intensities and different levels of legibility, readability and visibility, gives rise to poor readability. Due to the addition of a script font to the 76 Years of Central Lombok logo design. The results show that the choice of color intensity can influence the application of media to dark or light backgrounds. The author provides a solution in the form of using one color in one logo structure and the author also recommends that designers do not use script fonts in a logo so that typographic principles can be maximally applied in all media applications.